STUDENTS’ TARDINESS HABIT TO ATTEND THE CLASS AT THE STUDENTS OF STIE MUHAMMADIYAH MAMUJU - Hamzar Acha RH (IJIET (International Journal of Indonesian Education and Teaching), 2020)
This article aims at providing a description of students’ tardiness habit to attend the class at the very students of STIE Muhammadiyah Mamuju. This research employed qualitative research. The participants constituted nine students, three lecturers, and three administrators. The instruments were involvement observation, in-depth interview sheet, focus group discussion sheet, and additional questionnaire. The data were transcribed, reduced, and analyzed descriptively.  It discovered that there were lots of students’ internal tardiness inhibitions and external tardiness inhibitions which impeded the students to be puctual to attend the lectures. Students’ tardiness shared profoundly negative impacts on themselves, lecturers, and other punctual students. It is eligible not to allow the tardy students to attend the class if they are late for 1 minute. However, tardiness policy for 15 minutes is given only for unavoidable lateness as long as there is a confirmation to the lecturers or even administrators via phone before the class.